Carbon Nanotube-Graphene hybrid: Recent Synthesis Methodologies and Applications - Ijeomah, Geoffrey; Fahmi, Samsuri; Mohamad Adzhar, Md Zawawi; Obite, Felix (Penerbit Universiti Malaysia Pahang, 2017)
The melding of one-dimensional (1D) carbon nanotubes (CNTs) and two-dimensional (2D) graphene to generate a CNT-graphene hybrid with 3-dimensional (3D) features has generated a lot of scientific interest owing to the synergistic consequences of the resulting interface hybrid on the electrical, mechanical, electrochemical and optical properties, which presents plethora of opportunities in both fundamental research and device applications. The review presents an overview of the recent perspectives made in the field of CNT-graphene hybrid architectures. The possible applications particularly in device sensing, as well as challenges are also presented.